Mitigating Market Power in Banking: Cost Efficiency and the Path Toward Consumer Welfare - Mahjudin Mahjudin; Indriana Kristiawati; Muchammad Ilham SAM (Journal of Managerial Sciences and Studies, 2025)
Purpose – This study investigates the association between cost efficiency and the welfare performance of Islamic banks in Indonesia, focusing on the social costs of market power. The analysis covers both privately owned and state-owned Islamic banks over the period 2009–2017. Design/methodology/approach – The research utilizes Ordinary Least Squares (OLS), Fixed Effects (FE) panel regression, and Quantile Regression (QR) models to account for unobserved heterogeneity and improve policy applicability. To address potential endogeneity and reverse causality, the Two-Stage Least Squares Instrumental Variable (2SLS-IV) method is employed. Findings – Empirical results demonstrate a significant positive link between cost efficiency and banks’ welfare performance, implying that improving efficiency can mitigate welfare losses. Furthermore, the impact of cost efficiency on welfare outcomes varies depending on the bank’s familiarity with local market dynamics. QR results highlight that while cost efficiency may not eliminate welfare losses at the lower quantiles (Q.25–Q.50), it remains a critical factor in minimizing such losses.